Evaluation of Plant and Fungal Extracts for Their Potential Antigingivitis and Anticaries Activity. (19th February 2012) - Spratt, D. A.; Daglia, M.; Papetti, A.; Stauder, M.; O'Donnell, D.; Ciric, L.; Tymon, A.; Repetto, B.; Signoretto, C.; Houri-Haddad, Y.; Feldman, M.; Steinberg, D.; et al.
Abstract : The link between diet and health has lead to the promotion of functional foods which can enhance health. In this study, the oral health benefits of a number of food homogenates and high molecular mass and low molecular mass fractions were investigated. A comprehensive range of assays were performed to assess the action of these foods on the development of gingivitis and caries using bacterial species associated with these diseases. Both antigingivitis and anticaries effects were investigated by assays examining the prevention of biofilm formation and coaggregation, disruption of preexisting biofilms, and the foods' antibacterial effects. Assays investigating interactions with gingival epithelial cells and cytokine production were carried out to assess the foods' anti- gingivitis properties. Anti-caries properties such as interactions with hydroxyapatite, disruption of signal transduction, and the inhibition of acid production were investigated. The mushroom and chicory homogenates and low molecular mass fractions show promise as anti-caries and anti-gingivitis agents, and further testing and clinical trials will need to be performed to evaluate their true effectiveness in humans.